Kronik kalp yetersizliği olan hastalar için inanç ve uyum ölçeklerinin Türkçeye uyarlanması - (:unkn) unknown (My University, 2010)
Amaç: Kronik kalp yetersizliği (KKY) hastalarında İlaca Uyum Hakkındaki İnançlar Ölçeği (İUHİÖ), Diyete Uyum Hakkındaki İnançlar Ölçeği (DUHİÖ) ve Bireysel İzlem Hakkındaki İnançlar Ölçeği’nin (BİHİÖ) Türkçeye uyarlanmış şeklinin geçerlik ve güvenirliği araştırıldı. Çalışma planı: Türkçeye çevrilen ölçekler, dil geçerliği çalışması yapıldıktan sonra KKY’li 80 hastaya (47 erkek, 33 kadın; ort. yaş 59.3±12.5; dağılım 24-79) 15 gün ara ile iki kez yüz yüze görüşme ile uygulandı. Her bir ölçeğin iç tutarlığı Cronbach alfa katsayısı ile değerlendirildi. Ölçeklerin güvenirliğinin hesaplanmasında test-yeniden test için sınıfiçi korelasyon katsayısı kullanıldı. Bulgular: İki hafta ara ile uygulanan ölçeklerin her bir altboyutunun toplam puanları arasında anlamlı fark bulunmadı (p>0.05). İlk görüşmede üç ölçeğin yarar ve engel altboyutlarının Cronbach alfa değerleri sırasıyla İUHİÖ için 0.74 ve 0.59, DUHİÖ için 0.71 ve 0.58, BİHİÖ için 0.77 ve 0.68 bulundu. Test-yeniden test güvenirliğinde üç ölçeğin yarar ve engel altboyutlarının korelasyon katsayıları sırasıyla İUHİÖ için 0.90 ve 0.91, DUHİÖ için 0.86 ve 0.86, BİHİÖ için 0.90 ve 0.93 bulundu. Sonuç: Her üç ölçeğin de geçerlik ve güvenirliğinin yüksek olduğu bulundu ve ülkemizdeki KKY’li hastalarda geçerli ve güvenilir araçlar olarak kullanılabileceği sonucuna varıldı.

Objectives: We evaluated the validity and reliability of the Turkish versions of the Beliefs about Medication Compliance Scale (BMCS), Beliefs about Dietary Compliance Scale (BDCS), and Beliefs about Self-Monitoring Scale (BSMS) for patients with chronic heart failure (CHF). Study design: After language and content validity studies, the Turkish versions of the three scales were administered to 80 patients (47 men, 33 women; mean age 59.3±12.5 years; range 24 to 79 years) with CHF. Internal consistency of the scales was assessed using the Cronbach’s alpha coefficient. Test-retest reliability was assessed using the interclass correlation coefficient measured from two consecutive interviews interspersed by 15 days. Results: There were no significant differences between the two interviews with respect to the total scores of the benefit and barrier subscales of each scale (p>0.05). Cronbach alpha coefficients of the benefit and barrier subscales at the first interview were 0.74 and 0.59 for the BMCS, 0.71 and 0.58 for the BDCS, and 0.77 and 0.68 for the BSMS, respectively. Interclass correlation coefficients for test-retest reliability for the benefit and barrier subscales were as follows: 0.90 and 0.91 for the BMCS, 0.86 and 0.86 for the BDCS, and 0.90 and 0.93 for the BSMS, respectively. Conclusion: Our findings suggest that all three scales have high validity and reliability and can be used as valid and reliable instruments in Turkish patients with CHF.
Adaptation of the compliance and belief scales to Turkish for patients with chronic heart failure
Keywords: Mühendislik, Biyotıp